Faktor Internal dan Eksternal dan Strategi Pengembangan Agribisnis Porang (Studi kasus PT. Al-Fatih Porang Indonesia) - FM, A. Syahrul Ramadhan; Salengke, Salengke; Mahyuddin, Mahyuddin; Anita, Andi Suci (Universitas Galuh, 2024)
Porang (Amorphophallus muelleri Blume) is one type of tuber plant that is starting to be widely produced in Indonesia because it has high economic value. This is because porang is widely used in the food, health, cosmetic, and manufacturing industries. Over the last decade, the export volume has increased drastically. In 2020, the export value of Indonesian porang was dominated by Thailand with a market share of 59.3%, followed by China with a total of 130 shipments, or 47.84% of total porang exports. Export share to Thailand and Australia increased significantly in 2020, with an increase of 920.1% and 526.7%, respectively. The purpose of the study was to determine the internal and external factors that affect the development of porang and obtain strategies for porang development at PT Al-Fatih Porang Indonesia. Qualitative descriptive research with Porter's Diamond Theory to determine the competitive position of porang agribusiness and SWOT analysis to determine the internal and external factors of porang agribusiness at PT Al-Fatih Porang Indonesia The results of Porter's Diamond Theory analysis showed that in PT Al-fatih Porang Indonesia's conduct of porang agribusiness development, each subsystem has not been mutually supportive and related to each other. This can be seen in the marketing and agribusiness subsystem, which is still difficult. The appropriate strategy for the development of porang at PT. Al-Fatih Porang Indonesia is to optimise the utilisation of porang.